Microsoft networking fundamentals : LiveLessons - Liberman, Ed (LiveLessons., 2014)
"In this unique video package, top IT instructor/consultant Ed Liberman helps you master the core skills you need to run and manage networks, and fully prepare for your MTA 98-366 certification exam. Drawing on his experience helping thousands of people supercharge their IT careers, Ed helps you develop real world skills for success with networking -- and even have fun while you learn. Step by step, you'll build and deepen your knowledge of modern network infrastructures: both wired and wireless, local and wide area. Ed introduces hardware, protocols, services, and even basic network security concepts."--Resource description page.